EFFECT OF CR, DAR, DER, AND TATO ON THE PROFITABILITY OF LARGE TRADING COMPANIES - Sauh Hwee Teng; Peranika Hoddiana Sitanggang; Seri M Silitonga; Pengabdian Telaumbanua (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to test whether the Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Total Asset Turn Over (TATO) have an influence on the profitability of large trading companies on the IDX. The population in this study was 40 companies, with sample selection using purposive sampling technique so that 21 companies were studied in the 2017-2019 period, so the total data were 63 observations. However, because the data were not normally distributed, 19 data outliers were carried out, so that the total sample was 44 observational data. The approach used in this study is a quantitative and descriptive approach, with multiple linear regression methods. Based on the results of the study showed that partially Current Ratio (CR) has a positive effect on profitability, while Debt To Asset Ratio (DAR), Debt To Equity Ratio (DER), and Total Asset Turn Over (TATO) have a negative effect on profitability. The results of the simultaneous study of Current Ratio (CR), Debt To Asset Ratio (DAR), Debt To Equity Ratio (DER), and Total Asset Turn Over (TATO) have a positive effect on profitability